The validity and reliability of a novel activity monitor as a measure of walking - Ryan, C. G.; Grant, P. M.; Tigbe, W. W.; Granat, M. H. (British Journal of Sports Medicine, 2006)
Background: The accurate measurement of physical activity is crucial to understanding the relationship between physical activity and disease prevention and treatment.